Four weeks of supplementation with isolated soy protein attenuates exercise-induced muscle damage and enhances muscle recovery in well trained athletes: A randomized trial - Shenoy, S.; Dhawan, M.; Sandhu, J. S. (Asian Journal of Sports Medicine, 2016)
Background: The effects of consumption of isolated soy protein (ISP) for a chronic period (4 weeks) on exercise induced muscle damage (EIMD) in athletic population have never been explored..